2009
DOI: 10.1152/ajplung.00012.2009
|View full text |Cite
|
Sign up to set email alerts
|

Higher TRIP-1 level explains diminished collagen contraction ability of fetal versus adult fibroblasts

Abstract: Acute lung injury involving extremely immature lungs often heals without excessive fibrosis unlike later in gestation and in adults. Several factors may be involved, but fibroblast contraction of collagen has been linked to the level of wound fibrosis. To assess whether human lung fibroblasts of fetal versus adult origin differ in ability to contract collagen and define the molecular underpinnings, we performed three-dimensional collagen contraction assay, analyzed their differential mRNA profile, specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…We previously found that fetal human lung fibroblasts (HLF-F) lesser ability for collagen contraction is due to higher TRIP-1 protein expression [22]. To assess whether TRIP-1 drives fibroblast acquisition of myofibroblast phenotype and function in human lung fibroblasts, TRIP-1 siRNA-transfected versus control siRNA-transfected HLF-F were embedded in a 3D collagen matrix and studied for collagen contraction response and α-SMA expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously found that fetal human lung fibroblasts (HLF-F) lesser ability for collagen contraction is due to higher TRIP-1 protein expression [22]. To assess whether TRIP-1 drives fibroblast acquisition of myofibroblast phenotype and function in human lung fibroblasts, TRIP-1 siRNA-transfected versus control siRNA-transfected HLF-F were embedded in a 3D collagen matrix and studied for collagen contraction response and α-SMA expression.…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts were trypsinized, resuspended in cold, serum-free DMEM, and added to the collagen mixture at a final concentration of 5 × 10 5 cells/ml with 0.75 mg/ml as final collagen concentration [22]. Aliquots (in triplicate) were cast onto 24-well plates and allowed to solidify at 37°C (30–45 minutes), after which serum-free media was added, incubated, periodically observed for contraction, and photographed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed recently (20) that TRIP-1 is a novel modulator of fibroblast collagen contraction, an important step in wound repair and an event stimulated by TGF-␤1 action.…”
mentioning
confidence: 99%